Identification of mRNA-, circRNA- and lncRNA- Associated ceRNA Networks and Potential Biomarkers for Preeclampsia From Umbilical Vein Endothelial Cells - Chen, Dan; He, Biwei; Zheng, Panchan; Wang, Shuying; Zhao, Xueya; Liu, Jinyu; Yang, Xingyu; Cheng, Weiwei (Frontiers in Molecular Biosciences, 2021)
Objective: The etiology and pathogenesis of preeclampsia (PE) remain unclear, and ideal biomarkers for the early detection of PE are scarce. The involvement of the competing endogenous RNA (ceRNA) hypothesis in PE is only partially understood. The present study aimed to delineate a regulatory network in PE comprised of messenger RNAs (mRNAs), circular RNAs (circRNAs), long noncoding RNAs (lncRNAs), and microRNAs (miRNAs) via ceRNA profiles from human umbilical vein endothelial cells (HUVECs) to further reveal the pathogenesis of PE and potential biomarkers. Methods: Differentially expressed mRNAs, circRNAs, and lncRNAs were detected in HUVECs from early-onset preeclampsia (EOPE) cases and normal pregnancies by microarray analysis. Bioinformatics analysis was performed to systematically analyze the data, and a relevant ceRNA network was constructed. RNAs (ANGPT2, LIPG, hsa_circ_0025992, hsa_circ_0090396, hsa_circ_0066955, hsa_circ_0041203, hsa_circ_0018116, lnc-C17orf64-1:1, lnc-SLC27A2-2:1, and lnc-UEVLD-5:1) were validated by quantitative real-time PCR (qRT-PCR). Furthermore, expression of hsa_circ_0025992 was detected in maternal peripheral blood samples to confirm its potential as a novel biomarker. The receiver operating characteristic (ROC) curve was applied to analyze its diagnostic value. Results: Compared with HUVECs from normal pregnancies, HUVECs from EOPE cases had 33 differentially expressed mRNAs (DEmRNAs), 272 DEcircRNAs, and 207 DElncRNAs. GO and KEGG analyses of the DERNAs revealed the biological processes and pathways involved in PE. Based on the microarray data and the predicted miRNAs, we constructed a ceRNA network with 4 mRNAs, 34 circRNAs, 9 lncRNAs and 99 miRNAs. GO and KEGG analyses of the network reinforced the crucial roles of metabolic disorders, the p53 and JAK/STAT signaling pathways in PE. In addition, ROC analysis indicated that hsa_circ_0025992 could be used as a novel biomarker for PE. Conclusion: A novel ceRNA network was revealed in PE, and the potential of hsa_circ_0025992 to serve as a new biomarker was confirmed.